Longitudinal follow-up of quadriceps strength and function in a COPD cohort after 3 years. Issue 2 (10th August 2017) - Buttery, Sara C.; Mohan, Divya; Fisk, Marie; Hopkinson, Nicholas S.; Tal-Singer, Ruth; Wilkinson, Ian B.; Polkey, Michael I.
Skeletal muscle weakness is a distinct extrapulmonary manifestation of chronic obstructive pulmonary disease (COPD), which is associated with a poor prognosis [1] and may represent a novel therapeutic target [2]. However, there are only sparse longitudinal data from prospective studies on skeletal muscle weakness and its relationship with disease progression in COPD. Previous studies have been cross-sectional in nature, and have failed to correlate data with baseline measures of exercise performance or systemic inflammation. The short physical performance battery may be a useful endpoint in assessing impact on skeletal muscle dysfunction http://ow.ly/xf8z30dOFMz